A Comparison of Zinc and Carbon Doped on the Atomic Interdiffusion of InGaAs/AlGaAs Quantum Wells Laser Structures After Annealing - Paulus L. Gareso (Institut Teknologi Bandung, 2009)
We have compared a zinc and a carbon doped on the atomic interdiffusion of InGaAs/AlGaAs after annealing using Electrochemical capacitance voltage (EC-V), X-ray diffraction and photoluminescence (PL) measurements. Electrochemical capacitance voltage measurements revealed that the carrier concentration in the Zn-doped p++GaAs contact layers decreased after annealing at 900oC for 60 sec, indicating that some of the Zn acceptors were passivated or outdiffused from the surface. In contrast to the C-doped samples, an increase of carrier concentration was observed after annealing. X-ray rocking curve confirmed this result where the amount of lattice contraction increase after annealing which is attributed to the presence of the substitutional carbon CAs. Photoluminescence results showed that a large energy shift was observed in the Zn-doped samples compare with C- doped samples. Photoluminescence measurements after etching to various depth showed similar luminescence defects in both Zn- and C-doped samples. Photocurrent measurements showed the quality of quantum well was improve after annealing in C-doped samples due to activation of carbon doped.